Designing A Monitoring and Control System for A Production Line Based on The Internet of Things (IoT) - Abdussalam Ali Ahmed; Ahmed Salem Daw Alarga; Almabrouk Abdullah Almabrouk; Hesham Khaled Hesham; Mohammed Ramadhan Saeid (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2024)
The monitoring stage of the industrial process within establishments is considered an essential factor in the success of these establishments, in addition to being the basis for their continuation, because of the prominent role it plays in ensuring the avoidance of problems that may accompany the production process. Therefore, it is important when designing and implementing industrial facilities to take into account the monitoring process and how it can be performed optimally without negligence. In this paper, a production line was designed and implemented to transport products, which were classified according to their color into two basic categories.  ESP32 board was used to control the system, as this board provides the system with the ability to connect to the Internet for monitoring and controlling it remotely. It was tested, and the results obtained were good, as the operating status of the motors was displayed, in addition to turning the system on and off remotely through the Internet of Things technology provided by the ESP32 board